Thermal structure of a megadiverse Andean mountain ecosystem in southern Ecuador and its regionalization - Fries, Andreas; Rollenbeck, Rütger; Göttlicher, Dietrich; Nauß, Thomas; Homeier, Jürgen; Peters, Thorsten; Bendix, Jörg (ERDKUNDE, 2009)
The thermal structure of a megadiverse mountain ecosystem in southern Ecuador is examined on the basis of temperature measurements inside the natural mountain forest and at open-sites along an altitudinal gradient from 1600 to 3200 m. The main methodological aim of the current study is to develop an air temperature regionalization tool to provide spatial datasets on average monthly mean, minimum and maximum temperature by using observation data. The maps, based on data of the period 1999–2007, are needed by ecological projects working on various plots where no climate station data are available. The temperature maps are generated by combining a straightforward detrending technique with a Digital Elevation Model and a satellite-based land cover classification which also provides the relative forest cover per pixel. The topical aim of the study is to investigate the thermal structure of both manifestations of our ecosystem (pastures and natural vegetation) with special considerations to the ecosystem temperature regulation service by converting natural forest into pasture. The results reveal a clear thermal differentiation over the year, partly triggered by the change of synoptic weather situation but also by land cover effects. Thermal amplitudes are particularly low during the main rainy season when cloudiness and air humidity are high, but markedly pronounced in the relative dry season when daily irradiance and outgoing nocturnal radiation cause distinct differences between the land cover units. Particularly the lower pasture areas gained by slash and burn of the natural forest exhibit the most extreme thermal conditions while the atmosphere inside the mountain forest is slightly cooler due to the regulating effects of the dense vegetation. Thus, clearing the forest clearly reduces the thermal regulation function (regulating ecosystem services) of the ecosystem which might become problematic under future global warming.